Studying the pyroelectric effects of LiNbO3 modified composites - Zhang, Fan (2021)
LiNbO3 (LN) crystal has been widely used as a pyroelectric material due to its spontaneous electric polarization, which could be recharged easily and can directly convert heat energy into electricity. LN crystal's heat-resistant, low-cost, and low dielectric loss properties make it possible for its applications in room-temperature pyroelectric devices and thermal sensors. However, LN crystal suffers from fragility, inflexibility, and other mechanical properties, which limit its suitability for many applications in various fields. In this study, the LN modified flexible pyroelectric films, composed of LN micro-particles, polypropylene (PP) matrix, and multiwalled carbon nanotubes (MWCNTs), are successfully fabricated. The pyroelectric effects of LN crystal and LN/PP/MWCNT composite films are characterized by monitoring the patterned self-assembly of nanoparticles and the output pyroelectric currents. The excellent pyroelectric properties of the composites have potential applications in energy harvesters or sensors.